Editores, libreros y compradores: el estudio del mercado musical en España (1770-1808): Publishers, Booksellers, and Buyers: The Study of the Musical Market in Spain (1770-1808) - Marín, Miguel Ángel (Artigrama, 2022)
ResumenEn los últimos años, las narrativas historiográficas han mostrado una visión renovada de la música en la España de la Ilustración: la de un país que, con sus singularidades, supo mostrarse atento a los debates estéticos y las novedades de la cultura musical del momento. Esta perspectiva ha supuesto un viraje sustantivo frente a la idea heredada de un país retrasado, cuando no marginado, con respecto a la vida musical europea. En buena medida, este cambio de perspectiva ha sido posible gracias al estudio de un aspecto crucial como el mercado de la música. Este artículo propone una reflexión sobre las fuentes y la metodología apropiadas para la investigación de este mercado entre 1770 y 1808, en particular, de la red internacional de distribución que tuvo en esos años un extraordinario desarrollo. El análisis crítico que se presenta aquí sobre los agentes implicados, las dinámicas de difusión o el tipo de materiales en circulación, entre otros aspectos, podrá servir de guía para futuros estudios. Un mejor conocimiento del mercado musical permitirá entender las complejas dinámicas de transferencia cultural, en tanto que vinculadas a las fuentes musicales también viajaban prácticas estéticas y sociales asociadas al consumo de la música.AbstractIn  recent  years,  historiographical  accounts  have  shown  a  renewed  vision  of  music  in  Enlightenment  Spain:  that  of  a  country  that,  with  its  singularities,  knew  how  to  be  attentive  to  the  aesthetic  debates  and  the  novelties  of  the  musical  culture  of  the  time.  This  perspective  has  meant  a  substantial  departure  from  the  inherited  idea  of  a  country  that  lagged  behind,  if  it  was  not  marginalised,  with  respect  to  European  musical  life.  To  a  large  extent,  this  change  of  perspective  has  been  possible  thanks  to  the  study  of  a  crucial  aspect  such  as  that  of  music  market. This article proposes a reflection on the relevant sources and methodology for the investigation of the Spanish music market between 1770 and 1808, in particular, the international distribution network that underwent an extraordinary development in those years. The critical analysis  presented  here  on  the  agents  involved,  the  dynamics  of  dissemination  and  the  type  of  materials in circulation, among other aspects, can serve as a guide for future studies. A better knowledge  of  the  music  market  will  allow  us  to  understand  the  complex  dynamics  of  cultural  transfer,  insofar  as  the  aesthetic  and  social  practices  associated  with  music  consumption  were  also  linked  to  musical  sources.KeywordsMusic publishing, Musical market, Network, Published manuscript, Music-sellers, Editors, Buyers